2004
DOI: 10.1177/0363546503262161
|View full text |Cite
|
Sign up to set email alerts
|

Catastrophic Injuries in High School and College Baseball Players

Abstract: Suggestions for reducing catastrophic injuries in baseball include teaching proper techniques to avoid fielding and baserunning collisions, protecting the pitcher via a combination of screens and/or helmets with faceguards, continued surveillance and modifications of the bat and ball, eliminating headfirst slides, and continued analysis of chest protectors and automatic external defibrillators for commotio cordis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
70
0

Year Published

2008
2008
2021
2021

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 67 publications
(70 citation statements)
references
References 19 publications
(27 reference statements)
0
70
0
Order By: Relevance
“…Most of the available literature on severe injuries has focused solely on the high school population 6,[16][17][18][19][20] or catastrophic injuries [16][17][18][19][20][21][22][23] sustained in sports. Although previous researchers have briefly examined severe injuries in collegiate student-athletes in relation to overall injury patterns, we are the first to examine a large dataset of such injuries across multiple sports.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Most of the available literature on severe injuries has focused solely on the high school population 6,[16][17][18][19][20] or catastrophic injuries [16][17][18][19][20][21][22][23] sustained in sports. Although previous researchers have briefly examined severe injuries in collegiate student-athletes in relation to overall injury patterns, we are the first to examine a large dataset of such injuries across multiple sports.…”
Section: Discussionmentioning
confidence: 99%
“…Typically, the contact that occurs is only with surfaces in the environment, potentially decreasing the exposure to common severe-injury mechanisms during participation. Unlike previous researchers, 18 we also explored specific injuries and observed that most severe injuries were ACL tears, concussions, and hamstrings strains. Thus, our findings emphasize the need for concurrent prevention strategies for multiple injuries, particularly those related to the lower extremity and the head/face/neck.…”
Section: Common Injuries and Injury Mechanismsmentioning
confidence: 99%
“…[3][4][5][6] Although many of these changes are associated with reducing the incidence of injury related to player-to-player contact and noncontact, few researchers have examined injuries resulting from ball contact. Previous investigators have focused on ball-contact-related injuries as part of a cluster of all equipment-related injuries [7][8][9][10][11][12][13][14][15][16] or a mechanism of more catastrophic injuries 17 or in soccer-related discussions pertaining to heading and concussions 18 and surface type. 19 However, ball contact may be a common injury mechanism in sports with gameplay that focuses on a ball (eg, baseball, softball).…”
mentioning
confidence: 99%
“…6 Short-term effects of shoulder injuries include pain and reduction in athletic participation, whereas long-term effects can result in lifelong shoulder pain, instability, and osteoarthritis. 7 Previous epidemiologic surveys of shoulder injuries in athletes have focused on their occurrence in specific sports, [8][9][10][11][12][13][14][15][16][17] the mechanics of shoulder injuries in repetitive throwing sports, [18][19][20][21] risk factors of specific body part injuries (including shoulder) in specific sports, 5,[22][23][24][25] and diagnosis of particular types of shoulder injuries. 6,[26][27][28] One previous study investigated all shoulder injuries among high school athletes during 2 academic years.…”
mentioning
confidence: 99%